1998
DOI: 10.1002/(sici)1096-9837(199803)23:3<271::aid-esp867>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The character and age structure of valley fills in upper Wolumla Creek catchment, south coast, New South Wales, Australia

Abstract: Extensive valley fills at the base of the escarpment in upper Wolumla Creek, on the south coast of New South Wales, Australia, have formed from a combination of 'cut and fill' processes. The valley fills comprise series of alternating, horizontally bedded sand and mud units, reflecting reworking of detritus from deeply weathered granites of the Bega Batholith. Sand units are deposited as sand sheets or splays on floodplain surfaces or in floodouts that form atop intact valley fill surfaces downstream of discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Leigh et al ( 2010 ) suggest that this flow variability is essential in maintaining dryland river and wetland habitats and biodiversity. Similarly, some valley-bottom WiDs (also referred to as valley fill swamps, valley mire fens or ciénegas in literature) have been characterised by phases of incision, whether induced by crossing of an intrinsic geomorphic threshold, or by crossing of an extrinsic geomorphic threshold triggered by anthropogenic or climatic stressors (e.g., Fryirs and Brierley 1998 ; Tooth et al 2014 ; Pulley et al 2018 ; Grenfell et al 2019 , 2020 ). These types of systems oscillate spatio-temporally between palustrine valley-fill wetlands and incised gully networks over centennial to millennial timescales.…”
Section: Synthesis Of Articles and Emergent Research Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leigh et al ( 2010 ) suggest that this flow variability is essential in maintaining dryland river and wetland habitats and biodiversity. Similarly, some valley-bottom WiDs (also referred to as valley fill swamps, valley mire fens or ciénegas in literature) have been characterised by phases of incision, whether induced by crossing of an intrinsic geomorphic threshold, or by crossing of an extrinsic geomorphic threshold triggered by anthropogenic or climatic stressors (e.g., Fryirs and Brierley 1998 ; Tooth et al 2014 ; Pulley et al 2018 ; Grenfell et al 2019 , 2020 ). These types of systems oscillate spatio-temporally between palustrine valley-fill wetlands and incised gully networks over centennial to millennial timescales.…”
Section: Synthesis Of Articles and Emergent Research Themesmentioning
confidence: 99%
“…In addition to the potential impact of climate on sediment accumulation rates, Wiener et al ( 2022 ) postulate that seasonal cycles of desiccation of sediments in WiDs will likely strengthen phosphorus retention due to oxidation. Further, process dynamics in WiDs are equally as vulnerable as humid region wetlands to human-induced changes in riverine sediment flux, that may cause either siltation (e.g., Wolanski et al 2001 , Gell et al 2009 ) or erosion (Fryirs and Brierley 1998 ) of wetlands downstream.…”
Section: Synthesis Of Articles and Emergent Research Themesmentioning
confidence: 99%
“…Discontinuous gullies (or ‘independent’ gullies – Geyik, 1986) however form on the backslope and lower slopes of the valley side, which was a major, classifying factor introduced by Heede (1970). They do not join up with other gullies or stream networks but, instead, distribute their flow as fans over gentle slopes, or in valley‐fill aggradation in ponds or swamps, for example, the headwater ‘swampy meadows’/‘chain‐of‐ponds’/‘cut‐and‐fill’ landscapes (Eyles, 1977; Fryirs & Brierley, 1998; Prosser et al, 1994) described in south‐eastern Australia. Their discontinuity is explained by changes in slope gradient affecting the hydraulic capacity of the gully flows to deposit the eroded sediment from upslope.…”
Section: What Is a Gully?mentioning
confidence: 99%
“…A detailed understanding of trends in wetland sediment trapping dynamics at different temporal scales not only provides insight into catchment sediment budgets, but also into morphodynamic changes, resilience and evolutionary trajectories of these geomorphic landforms. Previous investigations that explored rates of vertical accretion at centennial and longer timescales have attempted to address the influence of geomorphological processes in the formation of valley‐bottom wetlands (e.g., Fryirs et al, 2014; Fryirs & Brierley, 1998; Pulley et al, 2018). Reported rates of long‐term sediment accretion in valley‐bottom wetlands, in a variety of climatic settings, were low and highly variable (0.01 to 0.40 cm year −1 ) (for review, see Wiener et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Valley‐bottom wetlands maintain a fragile balance between depositional and erosional processes, such that a change in the ratio of water to sediment supply may result in a significant shift in the dominant geomorphic processes (Grenfell et al, 2019). Studies on geomorphic processes have demonstrated that this wetland type alternates between multi‐decadal intervals of storage, followed by periods of net erosion (Fryirs & Brierley, 1998; Pulley et al, 2018). Thus, as many wetlands have the potential to intermittently recycle deposited fine sediment and associated phosphorous, they may contribute to downstream water quality deterioration (Fryirs et al, 2007).…”
Section: Introductionmentioning
confidence: 99%